2019
DOI: 10.1186/s13018-019-1169-y
|View full text |Cite
|
Sign up to set email alerts
|

Differences in bone mineral density of trajectory between lumbar cortical and traditional pedicle screws

Abstract: Background Cortical bone trajectory (CBT) has been well-known in spine surgery for obtaining improved fixation while minimizing soft tissue dissection. This study was designed to compare the bone mineral density (BMD) between the CBT and traditional trajectory (TT) by using Hounsfield unit (HU) values and identify the ideal decades of patients and the suitable lumbar segments using this CBT technology from a radiological standpoint. Methods Patients were selected random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 28 publications
2
14
0
6
Order By: Relevance
“…CBT was proven to be superior to the traditional screw as regards less intra-operative blood loss (23,27,29) , shorter operative duration (24,29), shorter length of stay (23,27,29) , higher bone density (20,12,30) , higher improvement in JOA score (16) , lower incidence of ASD (16,29) and overall lower incidence of complications (19,29) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBT was proven to be superior to the traditional screw as regards less intra-operative blood loss (23,27,29) , shorter operative duration (24,29), shorter length of stay (23,27,29) , higher bone density (20,12,30) , higher improvement in JOA score (16) , lower incidence of ASD (16,29) and overall lower incidence of complications (19,29) .…”
Section: Discussionmentioning
confidence: 99%
“…Sakaura et al (16) Compared with traditional screw: significantly higher improvement in JOA score, significantly lower ASD, non-statistically significant lower successful fusion rate Keorochana et al (19) Compared with traditional screw: significantly lower incidence of complications, nonstatistically significant different outcomes for pain VAS score (back and leg), disabilities score, JOA, intra-operative complications and fusion rates. Phan et al (20) Compared with traditional screw: greater bone density, but no difference in slippage at one year Asamoto et al (21) Significant improvement in JOA and VAS scores (100%), Bone fusion (89.1%) Gonchar et al (22) Fusion rate (99%), Compared with traditional screw: non-statistically significant higher improvement in JOA and VAS scores Marengo et al (23) Compared with traditional screw: Significantly shorter length of stay and less blood loss, significantly lower post-operative VAS and ODI scores, non-statistically significant higher fusion rate Sakaura et al (24) Compared with traditional screw: Significantly shorter operative duration and nonstatistically significant less intra-operative blood loss, higher recovery rate, less solid bony union, lower incidence of symptomatic ASD Wochna et al (25) Compared with pedicle screw: Significantly more intra-operative blood loss and nonstatistically significant shorter operative time and length of stay Hoffman et al (27) Compared with traditional screw: Significantly less intra-operative blood loss, shorter length of stay and non-statistically significant shorter operative time Karki et al (28) Compared with traditional screw, CBT has similar clinical outcome based on pain intensity, ODI status and JOA score as well as similar fusion rate and radiological evaluated complications Zhang et al (29) Compared with traditional screw: Significantly shorter operative duration and length of stay, less intra-operative blood loss, less incidence of complications, less incidence of ASD and ODI index Zhang et al (30) Compared with traditional screw: Significantly higher bone mineral density (9) Intra-operative cortical bone fracture at screw compression (8.3%) Rodriguez et al (10) No complications Glennie et al (11) Loss of reduction (50%), Screw loosening (37.5%) Ninomiya et al (15) Spacer backout (9.1%) Sakaura et al (16) Symptomatic ASD with need for additional reoperation (3.2%), Dural laceration (2.1%), Misplacement of pedicle screw (2.1%), Superficial wound infection (2.1%), Symptomatic hematoma (1.1%) Snyder et al (17) Thrombosis (3.8%), Hardware failure (2.5%), Pseudoarthrosis (2.5%), Deep wound infection requiring surgical debridement (1.3%), epidural hematoma (1.3%), Gonchar et al (22) Screw breakage (1.3%), Screw loo...…”
Section: Authorsmentioning
confidence: 99%
“…The HU value of the ROI selected in the CT transverse image was automatically calculated by the system. Zhang et.al [ 15 ] found that there was no difference in the HU values of the left and right sides of the same vertebral body in the same cross-section. Therefore, we averaged the HU values of the left and right ROI of the positioned cross-section respectively to represent the average HU value at 1/2 of the anterior part of the three parts of the upper, middle and lower parts of the vertebral body, thereby reflecting the bone mineral density of the vertebral body in this area indirectly [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…4 Com seu trajeto caudal-cranial e medial-lateral, espera-se obter uma maior força de fixação, particularmente em pacientes com osso osteoporótico e idosos, pois baseia-se no maior contato do parafuso com osso cortical denso. [5][6][7] Até onde se sabe, esta é a primeira vez que as dimensões do PTC em uma população americana são avaliadas e analisadas com relação ao sexo e nível da coluna vertebral.…”
Section: Discussionunclassified
“…Nesta técnica a inserção do parafuso segue o trajeto de distal para proximal no plano sagital e a direção lateral no plano transverso, isso aumenta o contato com o osso cortical no pedículo e no corpo vertebral, comparado ao método tradicional de fixação com PTP, conferindo uma maior resistência ao arrancamento. [5][6][7] Estudos biomecânicos demonstraram que a técnica de PTC alcança resultados na força de fixação equivalentes ou maiores ao método tradicional. [8][9][10] Figura 1: Parafuso trajeto pedicular (rosa); Parafuso trajeto cortical (laranja).…”
Section: Introductionunclassified